Quality of life in individuals with cervical dystonia before botulinum toxin injection in a Brazilian tertiary care hospital - Mariana Ribeiro Queiroz; Hsin Fen Chien; Egberto Reis Barbosa (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The purpose of this study was to evaluate quality of life (QoL) in a Brazilian population of individuals with cervical dystonia (CD) without effect of botulinum toxin (BTx) or with only residual effect of BTx, and identify possible physical and social aspects that affect their QoL. METHOD: Sixty five out of sixty seven consecutive patients with CD were assessed with two instruments: Short-form Health Survey with 36 questions (SF-36) and Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS). RESULTS: Severity of CD (TWSTRS) correlated moderately with two SF-36 subscale: role-physical (r= -0.42) and body pain (r= -0.43). Women also scored worse in two subscale of SF-36: vitality (p<0.05) and mental-health (p<0.005). CONCLUSION: Severity of CD and gender (female) were the main factors related to a worse QoL perception. These findings may help health professionals to predict which characteristics could lead to worse QoL, and therefore, better target their interventions to lessen the burden caused by CD.